IMPLEMENTASI PEDOMAN PERILAKU PENYIARAN DAN STANDAR PROGRAM SIARAN DI RADIO BANUA CORDIS DARIT - KABUPATEN LANDAK - Yohana Pomot E.21109082 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title of this research is the Implementation Of Guidelines Of Code Broadcasting And Standards Of Broadcasting Program In Banua Darit Cordis Radio – Landak Regency. Problems of this research are the portion of the commercial advertising schedule and public service announcements, also the discount of public service announcements on benua cordis radio did not appropiate to the rule of code broadcasting and standards broadcasting program on article 44 paragraphs 1 , 2 and 5. The goal of this research is to assess the implementation of  Banua cordis radio on guidelines of code broadcasting and and standards broadcasting program on article 44 , paragraphs 1,2 and 5 about the portion of the commercial advertising schedule and public service announcements, also the discount of public service announcements. This research used a descriptive research model with data processing techniques of qualitative analysis. It covers four things: a standard policy, resources, attitudes and communication. The results of the data analysis showed that the attitude of the parties in implementing the guidelines of code broadcasting and broadcast standard program on Article 44 , paragraph 1,2 and 5 about the portion of the commercial advertising schedule and public service announcements, also the discount of public service announcements which is exceed from the standard set by the government. Existing resources both of human resources, facilities and capital is still lacking and very limited . there is no intensive communication between radio and the government. The conclusion of this research is the banua Cordis Radio did not implement the government regulation about the guidelines of code broadcasting and broadcast standard program on article 44, paragraph 1,2 and 5. Key words: Code broadcasting, broadcast standard, police standard, resources broadcasting, behavior broadcasting, and communication.